MATHEMATICAL ISSUES IN TWO-DIMENSIONAL ARITHMETIC FOR ANALYZE STUDENTS' METACOGNITION AND CREATIVE THINKING SKILLS - Mohammad Tohir; Muhasshanah Muhasshanah (Fakultas Tarbiyah Universitas Ibrahimy, 2021)
This study aimed to analyze the level of students' metacognition skills and creative thinking in the generalization of a two-dimensional arithmetic sequence. A qualitative descriptive is a scientific approach used in this study. Students' of the Mathematics Education Study Program in Tarbiyah Faculty of Ibrahimy University are subjects in the study. Through this article, the author will describe the results of the research in the combinatorics course. The initial data was collected by assigning open problem-solving assignments to students and conducting documentation studies on students in generating arithmetic generalization patterns based on function formulae. Then, students are assigned to complete the second task, which is to compile a two-dimensional arithmetic sequence based on the multilevel function formula of arranged arithmetic. The analysis model of Miles and Huberman is the analytical methodology used in this study. The collected data indicated that the level of students’ creative thinking skills in combinatorics could be in the category of creative enough (16.67%), creative (50%), and very creative (33.33%). While the other analyzed data showed that the student’s level of metacognitive on level 3 (77.78%) and the remainder on level 4 (22.22%). These analysis results are influenced by several factors such as accuracy in compiling numbers and expanding data, conceptual mastery of arithmetic progression permutation concept, and its application, the tendency of students’ to rely on memorization and imitation of the examples.